Identification of Esters as Novel Aggregation Pheromone Components Produced by the Male Powder-Post Beetle, Lyctus africanus Lesne (Coleoptera: Lyctinae). - Titik Kartika; Nobuhiro Shimizu; Tsuyoshi Yoshimura (PLoS ONE, 2015)
Lyctus africanus is a cosmopolitan powder-post beetle that is considered one of the major pests threatening timber and timber products. Because infestations of this beetle are inconspicuous, damage is difficult to detect and identification is often delayed. We identified the chemical compounds involved in the aggregation behavior of L. africanus using preparations of crude hexanic extracts from male and female beetles (ME and FE, respectively). Both male and female beetles showed significant preferences for ME, which was found to contain three esters. FE was ignored by both the sexes. Further bioassay confirmed the role of esters in the aggregation behavior of L. africanus. Three esters were identified as 2-propyl dodecanoate, 3-pentyl dodecanoate, and 3-pentyl tetradecanoate. Further behavioral bioassays revealed 3-pentyl dodecanoate to play the main role in the aggregation behavior of female L. africanus beetles. However, significantly more beetles aggregated on a paper disk treated with a blend of the three esters than on a paper disk treated with a single ester. This is the first report on pheromone identification in L. africanus; in addition, the study for the first time presents 3-pentyl dodecanoate as an insect pheromone.